Does the logic of collective action explain the logic of corporatism? - Michael Wallerstein; Karl Ove Moene (University of Oslo, Department of Economics, 2003)
Mancur Olson's Logic of Collective Action has provided the dominant framework for understanding the impact of encompassing unions and employers confederations on wage-setting in Western Europe. In particular, scholars have drawn upon Olson's writing to descripe corporatism as a means for attaining the collective goods of low unemployment and low inflation in highly unionized labor markets. The strongest impact of corporatist institutions in the labor market, however, was to generate greater wage equality rather than superior macroeconomic performance. To understand the most important impact of corporatist institutions, a new framework that emphasizes the effect of wage-setting institutions on the distribution of wages and salaries is needed. In this paper, we present one component of such a framework with a model that illustrates how both employers and unions might gain by central agreements that reduce wage inequality relative to the equilibrium wage distribution with decentralized wage-setting.
Keywords: E24; J31; J51; 330; Wage setting; unions and employers confederations; corporatist institutions; Interessengruppentheorie; Interessenpolitik; Lohnbildung; Gewerkschaft